NILAI-NILAI PENDIDIKAN DALAM HADITS-HADITS TENTANG KEJUJURAN: ANALISIS TEMATIK DAN RELEVANSINYA TERHADAP PENGUATAN PENDIDIKAN KARAKTER - Inti Pitasari; Eka Mustika Riantina; Ahmad Ilham; Aziz Nur Wahid; M. Anugerah Saputra; Putri Marsya; Ratu Chielsa Riky. P; Wega Maria (ITB AAS Indonesia Surakarta, 2026)
Honesty is a fundamental value in Islamic teachings and plays a crucial role in shaping human character and moral conduct. Amid various moral challenges in educational settings, such as plagiarism, academic dishonesty, the misuse of digital technology, and declining student integrity, strengthening the value of honesty has become increasingly important. As one of the primary sources of Islamic teachings alongside the Qur'an, the Hadith of Prophet Muhammad (PBUH) contains educational values that serve as a foundation for character development. This study aims to analyze the educational values embedded in Hadiths concerning honesty using a thematic (maudhu'i) approach and to examine their relevance to strengthening character education. The study employed a qualitative approach with a library research method. Primary data consisted of authentic (ṣaḥīḥ) Hadiths related to honesty, while secondary data were obtained from relevant books, scholarly articles, and previous research. Data analysis involved the inventory of Hadiths, thematic classification, content analysis based on classical and contemporary syarah (Hadith commentaries), synthesis of educational values, and interpretation of their relevance to character education. The findings reveal that Hadiths concerning honesty encompass educational values such as integrity, trustworthiness (amanah), responsibility, exemplary conduct, and moral consistency. These values are interrelated in fostering students' noble character. Furthermore, the study demonstrates that the concept of honesty in the Hadith extends beyond interpersonal relationships by incorporating a spiritual dimension that nurtures continuous moral awareness. Therefore, Hadiths concerning honesty remain highly relevant as a conceptual foundation for strengthening character education in the contemporary era.